Cultura material e ressignificação do simbólico sagrado: rupturas e permanências através da percepção sonora - Sousa, Ana Maria da Silva Gomes de Oliveira Lucio de (2018)
This work has two main aims. The first consists in the intention of contributing to the studies concerning the relationship between mankind and sound production, in order to favour the theoretical and methodologic process of construction in the field of Archaeology. The second aim is to use that to answer certain questions related to the desacralization process of the modern world in Western societies.During the postgraduate course in Archaeology, in the module on the ancient Roman world, the initial idea appeared as the theoretical and methodologic difficulties to study sound productions and their relation with men and society, in that period and in ancient contexts, was dealt with.Nowadays, new possibilities to make analyses on such questions are approached in the area of recent organological studies, in the field that belongs to Archaeomusicology and to the area of Experimental Archaeology, for studies related to the production of musical instruments based on archaeological and textual sources. Recently, the field of Ethnoarchaeomusicology has flourished as an important tool under development. I search, in this sense, to develop a study to analyse the relationship between men and sound production in the field of study of Brazilian Historical Archaeology; to that aim, sound artefacts related to the cultural tradition of communities were chosen. With that intent, three artefacts were selected: the Ika flute, used by the Bororo ethnic group; the Adjá, employed in rituals belonging to religions of African roots; and the Shepherd Rattle, used by the herdsman in the Northeast of Brazil.The three artefacts are related to contexts that carry the dimensions of the social and cosmological role of the sound they produce, and this fact qualifies them to the second purpose of this study, which is investigate the desacralization order that manifests itself in the contemporary world.I decided for the shepherd rattle, firstly by observing the peculiarities about such artefact, and secondly because of my previous contact with individuals from communities linked to cattle raising during a period of approximately ten years, between 1985 and 1995, when I settled down and worked as a teacher in the municipality of Patos, in the agreste region of the State of Paraíba.The established theoretical and methodological route was intended to meet four questionswhich were held as the main lines: the social reproduction behaviour related to the sound production of the artefact; the production processes subjected to interference; the relation between this sound production and the dimensions of the sacred and the artefact itself. In this trajectory, a interdisciplinary dialogue was developed, situating research fields from the disciplines of History, Anthropology, Ethnology, Brazilian Historic Archaeology, Organology and Acoustics in order to obtain substantial information and answer to the initially proposed questions